Analysis of Battery Charging Using 100 Wp Solar Cells as Power Supply for Water Desalination Equipment: Teknologi - jefri kurniawan (Elektronika Sistem Senjata, 2024)
This study analyzed battery charging using a 100 Wp solar cell as apower source in a water desalination device. The main goal is to find out theamount of energy produced by the 100 W solar cell and the optimal batterycharging time. The research method involves the use of various components suchas solar charge controllers, 12-volt batteries, and inverters. The results showedthat the energy capacity stored in the battery reached 768 Wh, with the highestcharging efficiency on the fourth day of 137 Wh. Battery charging is affected by theintensity of sunlight, weather conditions, and the working position of the solar cell.Tests also show that the electrical energy generated can support the desalinationdevice for 10 hours with varying filling efficiency due to environmental factors. Thisresearch provides insight into the efficiency of solar power systems in varyingweather conditions and their practical applications in water desalination.